An evaluative survey on the illuminance level of artificial lighting related to student task performance of selected UP Diliman students - Quitiquit, Chelsea Alexis C.
The optimum amount of light can be hard to determine in spaces such as libraries, where different sight-dependent activities are done at the same time. This mixed method research determined how artificial lighting illuminance level and the layout in the Information Services and Instruction (ISI) section of the Main Library affected UP Diliman students task performance while they were inside the library. The study was conducted in the ISI Section of the Main Library mainly due to its accessibility and the fact that it is the only library open after regular work hours. Using a purposive sampling method, the study involved 50 UP Diliman students currently enrolled in any course and in any year, were willing to participate, and was in the ISI section for more than an hour. The study used an evaluative research design, where it examined the effects of the illuminance levels as experienced by its users. The following instruments were used for data gathering: laser measure, site observation sheet, illuminance meter, phone camera, and a self-designed questionnaire. The study used both qualitative and quantitative approach and was conducted in a period of two weeks in two phases, Phase I for site measurement and observation, and Phase II for the survey. Results revealed that even though the illuminance level in the library is low compared to the Illuminating Engineering Society of North America recommended illuminance standards, the students found that lighting was comfortable and was suitable to do tasks without feeling the negative effects of increased illuminance. Library layout is not influenced by lighting rather is arranged for functionality. The study only included 1 library and 50 students; therefore it is recommended that further study focusing on different libraries and more participants be conducted to yield comprehensive results.